2012
DOI: 10.1177/0003319711436078
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Predictors, and Impact of Peripheral Arterial Disease in Hemodialysis Patients

Abstract: We evaluated the prevalence, predictors, and outcome of peripheral arterial disease (PAD) among hemodialysis (HD) patients (n = 252) in a prospective study (3-year follow-up) conducted in Qatar. Those with PAD (n = 97; 38.5%) were older and more likely to be males and to have diabetes mellitus, prior coronary artery disease (CAD), or cerebrovascular disease. Diabetic retinopathy was an independent predictor of PAD (adjusted odds ratio: 2.7; P = .004). Women had a higher mortality. Three-year all-cause mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…[24] Several recent studies have shown an association between an abnormal ABI and overall and CV mortality. [4525] As the results of our observation period (maximum of 7 years) showed, PAD was an independent risk factor for all-cause and CV mortality.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[24] Several recent studies have shown an association between an abnormal ABI and overall and CV mortality. [4525] As the results of our observation period (maximum of 7 years) showed, PAD was an independent risk factor for all-cause and CV mortality.…”
Section: Discussionmentioning
confidence: 77%
“…[3] Recent data suggest that PAD is a strong predictor for overall mortality in hemodialysis (HD) patients. [45]…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study advocated a higher incidence of risk factors (PAD and peripheral neuropathy) for FU among HD patients [13]. In Qatar, an earlier report from our center identified a high incidence of PAD in HD patients [14]. However, there is a lack of information that describes the risk factors and prognostic implications of FU among HD patients in the Arab Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vascular disease prevention in these patients is important to reduce the incidence of cardiovascular events and the high morbidity and mortality [22]. Several recent studies have shown an association between an abnormal ABI and overall and cardiovascular mortality [3,4,23.] As shown in the results of our observation period (maximum of 6 years), PAD was an independent risk factor for all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 51%
“…Some experts have begun to pay attention to the importance of PAD and its biomarkers [2]. Recent data suggest that PAD is a strong predictor for overall mortality in hemodialysis (HD) patients [3,4]. Traditional risk factors alone do not explain the unacceptably high prevalence and incidence of CVD in ESRD patients [5].…”
Section: Introductionmentioning
confidence: 99%